Socialization and Training of Basic Gymnastics Movement Assessment Instruments For Junior High School Teachers - Herman Chaniago; Yafi Velyan Mahyudi; Wahyuningtyas Puspitorini; Desy Tya Maya Ningrum (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
Gymnastics is a fundamental sport crucial for the development of motor skills, strength, and coordination in junior high school students aged 13–15. However, its implementation in schools is often hampered by the limited availability of standardized assessment instruments and the low self-efficacy of PE teachers in teaching safe movement techniques. This Community Service activity aims to disseminate the basic gymnastics movement assessment instrument to physical education teachers in the Greater Jakarta area as an effort to standardize learning and evaluation. The implementation method is carried out through a participatory andragogical approach that includes face-to-face socialization, presentation of instrument materials, group discussions to gather input from practitioners, and a brief simulation of the use of assessment rubrics in the field. In addition, this program integrates technology through the digitization of the scoring system to improve data accuracy. The target outputs of this activity are the dissemination of the assessment instrument in target schools, increased teacher understanding of gymnastics movement parameters, and the preparation of accountable activity reports and documentation. Through this activity, synergy is created between academics and practitioners in improving the quality of physical education and providing valid, reliable, and safe evaluation references for students at the junior high school level.